Morphology, Thermal, and Mechanical Characterization of Bark Cloth from Ficus natalensis. (31st August 2013) - Rwawiire, Samson; Luggya, George William; Tomkova, Blanka
Abstract : The United Nations Educational, Scientific and Cultural Organization (UNESCO) proclaimed in 2005 that Ugandan bark cloth is largely produced from mutuba tree ( Ficus natalensis ) as a "Masterpiece of the Oral and Intangible Heritage of Humanity." An exploratory investigation of bark cloth a nonwoven material produced through a series of pummeling processes from mutuba tree in Uganda is fronted as a prospective engineering natural fabric. Bark cloth was obtained from Ficus natalensis trees in Nsangwa village, Buyijja parish in Mpigi district, Central Uganda. The morphology of the fabric was investigated using scanning electron microscope (SEM). thermal behavior of the fabric was studied using thermagravimetric analysis (TGA) and differential scanning calorimetry (DSC). Fourier transform infrared spectroscopy was used to evaluate the surface functional groups. The fabric was subjected to alkaline treatment for six hours at room temperature in order to study the change in fabric thermal properties so as to set a base for applications in biodegradable composites. Findings show that the natural nonwoven fleece is stable below 200°C; alkaline treatment positively influences the thermal behavior by increasing the onset of cellulose degradation temperature. The fabric morphology showed that it is made up of fairly ordered microfibers which can be beneficial for nanocomposites.